Implementasi Manajemen Perpustakaan Berbasis Web - Karisma, Viki Eka; Adhiwibowo, Whisnumurti (Information Science and Library, 2022)
The problem in this research is how the implementation of library management in Porangparing Village. While the findings in the field, in terms of service, the village library is also quite good. borrowing books and returning books are also required to follow the existing procedures. However, the application system for library technology and data collection in the village library is still manual. Members or residents who are late in returning books or destroying books will be fined or subject to sanctions determined by the library. Library management is the process of planning, organizing, implementing and controlling library management of library management in organizations that have been established in the village library. Meanwhile, in improving the library, the staff also motivated the villagers to increase their reading interest in the library. The system design is carried out using a modeling language using UML. While the programming used is PHP using the MySQL database. The final result of this design   produces a web-based library information system which aims to make it easier for officers to manage book data so that errors do not occur. The system design is carried out using a modeling language using UML. While the programming used is PHP using the MySQL database. The final result of this design produces a web-based library information system which aims to make it easier for officers to manage book data so that errors do not occur.Permasalahan dalam penelitian ini adalah bagaimana implementasi manajemen perpustakaan di Desa Porangparing. Sedangkan temuan yang ada di lapangan, Segi pelayanan nya perpustakaan desa juga sudah cukup baik. peminjaman buku dan pengembalian buku juga diharuskan mengikuti prosedur yang sudah ada. Namun sistem penerapan tekhnologi perpustakaan serta pendataan di perpustakaan desa masih manual. Bagi anggota atau warga yang telat memulangkan buku atau merusak buku akan di denda atau dikenakan sanksi yang telah ditentukan oleh perpustakaan tersebut.   Manajemen perpustakaan adalah proses perencanaan, pengorganisasi-an, pelaksanaan dan kontrol terhadap manajemen perpustakaan terhadap manajemen perpustakaan dalam organisasi yang telah dibentuk di perpustakaan desa tersebut. Sedangkan dalam meningkatkan perpustakaan serta petugas ikut memotivasi para warga desa dalam meningkatkan minat baca di perpustakaan.   Perancangan sistem dilakukan dengan bahasa pemodelan dengan menggunakan UML. Sedangkan pemograman yang dipakai adalah PHP dengan menggunakan database MySQL. Hasil akhir perancangan tersebut menghasilkan suatu sistem informasi perpustakaan berbasis web yang bertujuan untuk memudahkan bagi petugas dalam mengelola data buku supaya tidak terjadinya kesalahan. Perancangan sistem dilakukan dengan bahasa pemodelan dengan menggunakan UML. Sedangkan pemograman yang dipakai adalah PHP dengan menggunakan database MySQL. Hasil akhir perancangan tersebut menghasilkan suatu sistem informasi perpustakaan berbasis web yang bertujuan untuk memudahkan bagi petugas dalam mengelola data buku supaya tidak terjadinya kesalahan.